Music Education for Surviving and Thriving: Cultivating Children’s Wonder, Senses, Emotional Wellbeing, and Wild Nature as a Means to Discover and Fulfill Their Life’s Purpose - Smith, Tawnya D. (Frontiers in Education, 2021)
Children who are supported throughout childhood and adolescence to both maintain their sense of wonder in nature, and honor and explore their wild human nature, are well positioned to mature into soulcentric adults capable of living into their purpose in service to both their culture and the whole of life. However, our society’s ecocidal culture and unjust institutions often replicate oppressions and promote egocentric behaviors that preclude thriving. Additionally, many children are alienated from nature and are thought to have nature-deficit disorder, which can include both mental and physical maladies. In this article I explore conceptions of ecojustice education to further illustrate pathways for curriculum development in music education that might encourage children and adolescents to maintain their sense of wonder in nature, fully develop their sensory capacities, support their mental and emotional wellbeing, attune more carefully to their wild nature and soul’s purpose, and contribute to the environmental and social commons—all which might support human flourishing and the continued survival of our species.